THE CASE FOR PROBABILISTIC FORECASTING IN HYDROLOGY - Krzysztofowicz R. (My University, 2001)
That forecasts should be stated in probabilistic, rather than deterministic, terms has been argued from common sense and decision-theoretic perspectives for almost a century. Yet most operational hydrological forecasting systems produce deterministic forecasts and most research in operational hydrology has been devoted to finding the 'best' estimates rather than quantifying the predictive uncertainty.This essay presents a compendium of reasons for probabilistic forecasting of hydrological variates. Probabilistic forecasts are scientifically more honest, enable risk-based warnings of floods, enable rational decision making, and offer additional economic benefits. The growing demand for information about risk and the rising capability to quantify predictive uncertainties create an unparalleled opportunity for the hydrological profession to dramatically enhance the forecasting paradigm.
Keywords: HYDROLOGY; METEOROLOGY; HYDROLOGICAL METHODS; PRECIPITATION; RUNOFF; FLOODS; PROBABILITY; STATISTICAL DISTRIBUTION; DECISION-MAKING